Cranberry Juice Ingestion and Clinical Drug-Drug Interaction Potentials; Review of Case Studies and Perspectives - Nuggehally R Srinivas (Frontiers Media S.A., 2013)
Cranberry juice is a popular beverage with many health benefits. It has anthocyanins to supplement dietary needs. Based on in vitro evidence cranberry juice is an inhibitor of CYP enzymes and at higher amounts as potent as ketoconazole (CYP3A) and fluconazole (CYP2C9). There is, however, a discrepancy between in vitro and in vivo observations with respect to a number of substrates (cyclosporine, warfarin, flurbiprofen, tizanidine, diclofenac, amoxicillin, ceflacor); with the exception of a single report on midazolam, where there was a moderate increase in the AUC of midazolam in subjects pre-treated with cranberry juice. However, another study questions the clinical relevancy of in vivo pharmacokinetic interaction between cranberry juice and midazolam. The controversy may be due to a) under in vitro conditions all anthocyanin principles may be available to have a concerted effort in CYP inhibition; however, limited anthocyanin principles may be bioavailable with varying low levels in the in vivo studies; b) a faster clearance of the active anthocyanin principles under in vivo conditions may occur, leading to low threshold levels for CYP inhibition; c) efficient protein binding and/or rapid tissue uptake of the substrate may have precluded the drug availability to the enzymes in the in vivo studies. With respect to pharmacodynamic aspects, while the debate continues on the issue of an interaction between warfarin and cranberry juice, the summation of the pharmacodynamics data obtained in patients and healthy subjects from different prospectively designed and controlled clinical trials does not provide overwhelming support for the existence of a pharmacodynamic drug interaction for normal cranberry juice ingestion. However, it is apparent that consumption of large quantities of cranberry juice (about 1-2 L per day) or cranberry juice concentrates in supplements for an extended time period (>3-4 weeks) may temporally alter the effect of warfarin. Therefore, the total avoidance of cranberry juice by warfarin users may not be warranted by the published studies. However, in certain situations of higher intake of cranberry juice or concentrate there may be a need to monitor both warfarin doses and its effect. This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.